2011
DOI: 10.1002/hipo.20791
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency stimulation of the temporoammonic pathway induces heterosynaptic disinhibition in the subiculum

Abstract: The subiculum (Sub) is the principal target of CA1 pyramidal cells. It serves as the final relay of hippocampal output and thus mediates hippocampal-cortical interaction. In addition, the Sub receives direct input from the entorhinal cortex via the temporoammonic pathway. In this study, we demonstrate that low-frequency stimulation of the temporoammonic pathway results in the disinhibition of excitatory synaptic transmission at CA1-Sub synapses. We provide evidence that this disinhibition is mediated by an NMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…As in all experiments GABA A receptor-mediated transmission was blocked by bicuculline (5-10 µM), the concentration of MgSO 4 and CaCl 2 was elevated to 4 mM each in the recording medium in order to prevent epileptiform discharges [27][29]. In previous work we showed that increased Mg 2+ - and Ca 2+ -levels as well as blockade of inhibition are not related to bursting [30], [31].…”
Section: Methodsmentioning
confidence: 84%
“…As in all experiments GABA A receptor-mediated transmission was blocked by bicuculline (5-10 µM), the concentration of MgSO 4 and CaCl 2 was elevated to 4 mM each in the recording medium in order to prevent epileptiform discharges [27][29]. In previous work we showed that increased Mg 2+ - and Ca 2+ -levels as well as blockade of inhibition are not related to bursting [30], [31].…”
Section: Methodsmentioning
confidence: 84%
“…Of relevance to the present study, the term temporoammonic pathway (“TA path”) has been widely adopted in physiological studies (Maccaferri and McBain, 1995 ; Dvorak-Carbone and Schuman, 1999 ; Ang et al, 2005 ; Fidzinski et al, 2011 ; Booth et al, 2016 ). This term is used to refer to a direct entorhinal projection to CA1 and these fibers are discussed as though they are independent from PP (Dvorak-Carbone and Schuman, 1999 ).…”
Section: Discussionmentioning
confidence: 99%